DIGITAL CONTRAST VENOGRAPHY IN VIVO OF THE FORELIMB AND HINDLIMB IN HEALTHY SHEEP AND GOAT - Santos, Ivan F. Charas (2018)
Abstract The venographic examination allows diagnosing and treating foot diseases. It can be the basis of studies about the administration of medication in the hoof region. The aim of the study was to describe the venographic pattern in the distal region of the forelimb and hindlimbs of healthy sheep and goats, as well as to compare vascularization between them. Ten clinically healthy sheep and goats, five male and five female of different breeds, aged 2 to 4 years and weighing 45 to 63 kg were used. The forelimbs and hindlimbs were subjected to contrast venography of the distal region. The venograms were taken in a digital X -ray machine and analyzed in the EcoView® software. The veins of the metacarpus and metatarsus; and the proximal, middle and distal phalanges of the forelimbs and hindlimbs of sheep and goats were identified 25-30 seconds after contrast injection. The technique error observed during the venography was the contrast perivascular extravasation. The venograms showed the vascularization in the distal region of forelimbs and hindlimbs and the communication of vessels between them. The better radiographic view to evaluate the vessels was the lateral projection. The normal venous pattern of the distal region of forelimbs and hindlimbs of sheep and goats could be observed by venography.